2011
DOI: 10.1111/j.1399-0004.2011.01659.x
|View full text |Cite
|
Sign up to set email alerts
|

BAG3‐related myofibrillar myopathy in a Chinese family

Abstract: In contrast to the usual slow disease progression in myofibrillar myopathies, patients with Bag3opathy often have a rapidly progressive and more severe phenotype with a worse prognosis. We describe a Chinese patient, born to non-consanguineous parents, who first presented at age 6 with clumsy walking and difficult climbing staircase. With a history of restrictive lung disease previously diagnosed as asthma, she progressed rapidly with proximal myopathy, rigid spine and bilateral tightening of the Achilles tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 27 publications
9
67
0
Order By: Relevance
“…Although the Arg258Trp mutation was recently reported in a Chinese patient with MFM, it was also found in the unaffected father of the patient and the patient carried another mutation Pro209Leu [Lee et al, 2011]. In this study, we demonstrated that the MFM-associated Pro209Leu mutation impaired the differentiation of skeletal muscle cell line C2C12, although it caused no functional alterations in the NRCs and in a cardiomyocyte cell line H9c2.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Although the Arg258Trp mutation was recently reported in a Chinese patient with MFM, it was also found in the unaffected father of the patient and the patient carried another mutation Pro209Leu [Lee et al, 2011]. In this study, we demonstrated that the MFM-associated Pro209Leu mutation impaired the differentiation of skeletal muscle cell line C2C12, although it caused no functional alterations in the NRCs and in a cardiomyocyte cell line H9c2.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, Bag3 knockout mice displayed degeneration of muscle fibers with apoptotic nuclei in the striated muscles, resulting in a severe form of skeletal myopathy and cardiomyopathy, which lead to a hypothesis that BAG3 protein might play a role as a Z-disc signaling molecule [Homma et al, 2006]. In accordance with the hypothesis, apart from the association with DCM described above [Norton et al, 2011;Villard et al, 2011], a heterozygous Pro209Leu mutation was found in patients with myofibrillar myopathy (MFM) accompanied by cardiomyopathy (MFM6; MIM# 612954) [Lee et al, 2011;Odgerel et al, 2010;Selcen et al, 2009]. Moreover, it was demonstrated that knockdown of bag3 in a zebrafish model developed heart failure resembling to human DCM [Norton et al, 2011].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Pathology: atrophic fibres; focal myofibrillar disorganisation and degeneration; sarcoplasmic accumulation of granulofilamentous material. Classified as MFM [227] c.652C>T…”
Section: P209w + R258w 6 Skelmentioning
confidence: 99%
“…Since then 10 additional Bag3 mutations have been reported of which nine result in DCM [225,226] and one in MFM [227] (Table 7). BAG3 is one of six members of the BAG family of proteins.…”
Section: Bag3 and Bag3opathiesmentioning
confidence: 99%